THE MODERATING EFFECT OF THE CONCENTRATION OF INSTITUTIONAL INVESTORS IN THE RELATION BETWEEN EARNINGS SURPRISE AND ABNORMAL RETURNS - Galhoti Coelho, Éverton; Colauto, Romualdo Douglas (Advances in Scientific and Applied Accounting, 2021)
Objectives: The objectives of the article are: (i) to identify the determinants of default of real estate financing and (ii) to verify the existence of influence of the individual context (bank branch) on default. Method: The article studied 5,113 real estate financing contracts of individuals belonging to 1,448 branches of a national financial institution in force on September 30, 2019. Due to the multilevel character of the sample (level 1: individual and level 2: bank branch) and considering that the different bank branches present different levels of performance (in different indicators, including the percentage of defaulted real estate financing contracts), the multilevel logistic model was used to the detriment of the traditional logistic model. Results: The multilevel logistic model was superior to the traditional logistic model (18.8% of the default probability variability refers to the bank branchlevel). The negatively significant characteristics of the individual are: age, length of relationship, receiving salary at the bank and higher education level, and the positively significant characteristics are: level of education up to elementary school and the financing/income ratio. The variables gender and marital status were not significant. Contributions: The innovations of the article are: (a) the national coverage of the sample on default by individuals, (b) the use of two unprecedented variables and (c) the use of the multilevel logistic model. The identification that individuals with the same characteristics, however coming from different bank branches, have different probabilities of defaulting leads to the knowledge of academics and professionals in the area the recommendation of hierarchical modeling for the analysis of real estate credit.